2007
DOI: 10.1161/01.str.0000252159.05702.00
|View full text |Cite|
|
Sign up to set email alerts
|

MRI Monitoring of Neuroinflammation in Mouse Focal Ischemia

Abstract: Background and Purpose-A growing body of evidence suggests that inflammatory processes are involved in the pathophysiology of stroke. Phagocyte cells, involving resident microglia and infiltrating macrophages, secrete both protective and toxic molecules and thus represent a potential therapeutic target. The aim of the present study was to monitor phagocytic activity after focal cerebral ischemia in mice. Methods-Ultrasmall superparamagnetic particles of iron oxide (USPIO) were intravenously injected after perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 34 publications
8
82
1
Order By: Relevance
“…Recently, several studies have reported the use of magnetic nanoparticles to identify inflammatory regions in stroke (4,(23)(24)(25). However, magnetic nanoparticles detect only macrophages/ microglia, which are thought to be less associated with acute inflammatory damage in stroke and do not correlate with infarct size, whereas neutrophil infiltration and MPO correlated well with infarct size (5).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have reported the use of magnetic nanoparticles to identify inflammatory regions in stroke (4,(23)(24)(25). However, magnetic nanoparticles detect only macrophages/ microglia, which are thought to be less associated with acute inflammatory damage in stroke and do not correlate with infarct size, whereas neutrophil infiltration and MPO correlated well with infarct size (5).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these hyperintensities is also associated with weakened effect of antidepressant treatment, as well as long-term disability and neuro-cognitive decline (79). While the inflammatory response around the site of stroke is a well-known clinical observation (80) an animal model of focal ischemia demonstrated that inflammation extends far beyond the original site of ischemic injury, predominantly mediated by microglia (81). This is exactly the same manner by which stress has been attributed to the cause of neuroinflammation in various animal models (82), which has led to formulation of a neuroinflammatory hypothesis of depressive illness (83).…”
Section: Neuroinflammation and Its Implication In The Pathophysiologymentioning
confidence: 99%
“…Another application for T 2 *-weighted images is the detection of susceptibility agents such as contrast agents. Systemic intravenous administration of ultrasmall superparamagnetic iron oxide nanoparticles for phagocytosis by activated blood-borne macrophages as a method to image the peripheral inflammatory response after stroke is one such application (Rausch et al, 2002;Wiart et al, 2007). However, evidence indicates this technique may not be so robust (Desestret et al, 2009;Henning et al, 2009), and more variability has been observed in the clinical setting Nighoghossian et al, 2007;Saleh et al, 2007).…”
Section: Relaxometrymentioning
confidence: 99%